Peningkatan Minat dan Kemampuan Santri Pondok Pesantren Al Ashry di Bidang Matematika Melalui Pendekatan Small Group Discussion - Izzati Rahmi HG; Admi Nazra; Hazmira Yozza; Ferra Yanuar; Budi Rudianto; Susila Bahri; Narwen Narwen; Maiyastri Maiyastri; Haripamyu Haripamyu; Riri Lestari; Yudiantri Asdi; Efendi Efendi; Dodi Devianto; Zulakmal Zulakmal; Ahmad Iqbal Baqi; Arrival Rince Putri; Radhiatul Husna; Nova Noliza Bakar; Mawanda Almuhayar; Ikhlas Pratama Sandi (Warta Pengabdian Andalas, 2023)
Mathematics is a field of study needed in various aspects of life. Accordingly, mathematics should always be considered a compulsory subject at every level of education, including in Islamic Boarding Schools. The fact shows that implementing mathematics learning in several schools needs to run optimally, especially in schools lacking teachers and limited educational facilities and infrastructure, such as The Al Ashry Islamic Boarding School, at the secondary level in Padang. This condition indicates that it is necessary to assist other parties to help students in their mathematics learning process. For this reason, the community service team of The Mathematics and Science Data Department of Andalas University conducted an intensive mathematics tutoring activity for The Al-Asyri Boarding School students. The activity carried out during September-December 2022 combined the lecture and the small group discussion approach. From the evaluation delivered by the students at the end of the activity, it can be concluded that this activity increased students’ interest, motivation, efficacy, and understanding of mathematics subject.